2008
DOI: 10.1108/01437720810904194
|View full text |Cite
|
Sign up to set email alerts
|

Human resource practices, organizational commitment and intention to stay

Abstract: Purpose -The purpose of this paper is to examine the impacts of key human resource (HR) practices on permanent employees' organizational commitment and intention to stay. These practices include facilitating of person-organization fit (p-O fit), designing effective remuneration and recognition, creating sufficiently challenging assignments, and implementing training and career development. Design/methodology/approach -The study was carried out in three phases. First, 13 experts (e.g. academics, HR managers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
257
4
17

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(307 citation statements)
references
References 81 publications
(88 reference statements)
29
257
4
17
Order By: Relevance
“…This is not in line with the human capital perspective; hence hypothesis 1 is rejected. In recent paper, Chew and Chan (2008) also showed that 'training and career development' has no significant effect on employees' intentions to stay with the firm. As expected from the social exchange theory, participation in general training is positively associated with PSED.…”
Section: Training Psed and Intentions To Quitmentioning
confidence: 99%
“…This is not in line with the human capital perspective; hence hypothesis 1 is rejected. In recent paper, Chew and Chan (2008) also showed that 'training and career development' has no significant effect on employees' intentions to stay with the firm. As expected from the social exchange theory, participation in general training is positively associated with PSED.…”
Section: Training Psed and Intentions To Quitmentioning
confidence: 99%
“…Compensation plays a vital role in attracting employees and influencing http://www.sajhrm.co.za Open Access individuals to greatly commit to the organisation (Chew & Chan, 2008). It was also emphasised that employees work for the sake of earning a salary or wage.…”
Section: Retention Factors and Intention To Leavementioning
confidence: 99%
“…Besides mediation and arbitration, control, acceptance and elimination are also other strategies for managing conflict as identified by Chew and Chan (2008). Wood (2005) in consonance with the identification strategy by Chew and Chan (2008) described control as the tendency to bring tension and emotions down to a level at which productive discussion and negotiation can occur. The author added that humour is often an effective tool here as well as the use of temporary breaks or time-outs in the discussion between conflicted parties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It therefore depends on the situation. According to Chew and Chan (2008), there are five strategies for managing conflict which include mediation (identifying multiple possible alternatives and mutually select one that is acceptable to all involved parties and in the interest of organisation), arbitration (this requires provision of a safe and productive opportunity for the conflicted parties to air their disagreements). After careful listening to each party, formulate, define and provide solution to the parties.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation